2011
DOI: 10.1007/s00436-011-2746-0
|View full text |Cite
|
Sign up to set email alerts
|

Control strategies using diclazuril against coccidiosis in goat kids

Abstract: Coccidiosis is probably the main parasitic disease affecting goat kids around the weaning period, leading to high economic losses in goat production due to deaths and delayed growth rates of infected animals. A total of 101 kids of 2-4 weeks of age, naturally infected with Eimeria spp., were divided into five groups and studies were conducted to analyse the effects of metaphylactic administration of diclazuril (Vecoxan®) on parasitological and productive parameters. Two different doses of diclazuril (1 and 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…According to Peek and Landman [87], the use of Diclazuril (0.5 mg/ml) showed a significant reductive efficiency on sporulated Eimeria oocysts after 24 h of incubation compared to our results, while the sulfaquinoxaline showed a slight reduced oocysts number. Indeed, in agreement with our observations, many investigations demonstrated that the in vitro anticoccidial effect of diclazuril is high [88,89]. This difference may be attributed necessarily to pharmacological properties of drugs and their action on coccidia development.…”
Section: Discussionsupporting
confidence: 92%
“…According to Peek and Landman [87], the use of Diclazuril (0.5 mg/ml) showed a significant reductive efficiency on sporulated Eimeria oocysts after 24 h of incubation compared to our results, while the sulfaquinoxaline showed a slight reduced oocysts number. Indeed, in agreement with our observations, many investigations demonstrated that the in vitro anticoccidial effect of diclazuril is high [88,89]. This difference may be attributed necessarily to pharmacological properties of drugs and their action on coccidia development.…”
Section: Discussionsupporting
confidence: 92%
“…This showed that the treatment selected had failed and indicated that there was a need to improve the metaphylaxis method in order to achieve a reduction in oocyst shedding and thereby decrease the environmental contamination. As proposed by Ruiz et al (2012), on goat farms with a history of serious clinical caprine coccidiosis, precise timing of treatments using the anticoccidial drug diclazuril improves the control over coccidiosis in the farm and prevents severe clinical status (RUIZ et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It affects the profitability of the industry, particularly in rural, semi-arid geographic regions that are economically dependent on goat rearing, such as the Mediterranean basin (RUIZ et al, 2006), Africa (KANYARI, 1993), Asia (FAIZAL;RAJAPAKSE, 2001) and Latin America (CAVALCANTE et al, 2012). Economic losses result from the high mortality rate among goat kids, reduction of productivity and delayed weight gains of parasitized animals (LIMA, 2004;RUIZ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eimeria ninakohlyakimovae has been reported as one of the most pathogenic Eimeria species, able to produce a massive destruction of infected epithelial host cells resulting in either mild non-haemorrhagic infections (Dai et al 2006) or severe haemorrhagic typhlocolitis even with fatal outcome (Ruiz et al 2013). Goat rearing is increasing all over the world, but particularly in emerging countries (FAOSTAT 2013), so there is an urgent need for efficient control strategies to ensure that the goat market remains a solid source of meat, milk and dairy products (Ruiz et al 2012). Importantly, no new anti-coccidial drugs have been released into the market for many decades.…”
Section: Introductionmentioning
confidence: 99%